Strategi Komunikasi Pemasaran Brand Skincare Mako by Seris dalam Meningkatkan Engagement melalui Media Sosial - Yanti, Aulia Rahma (Dimar Jaya Publishing, 2023)
The aim of the research is to understand the marketing communication strategy for the Skincare Mako by Seris brand to increase engagement on social media. This research uses descriptive qualitative research methods. The research results show that the marketing communication strategy for the skincare brand Mako by Seris utilizes the golden time, namely the first three seconds with clickbait sentences. Apart from that, the marketing communication strategy for the Skincare Mako by Seris brand uses soft selling and hard selling marketing communication elements in conveying information by constructing organized sentences. The total engagement obtained through TikTok video content per week is 0.65% of the overall results (2.55%). This figure is still below the average engagement standard at the normal level, namely 5.3%. For this reason, Mako by Seris held live streaming activities to increase its performance and succeeded in increasing consumer engagement by 1.6% weekly.